Dinámica de la desigualdad regional en México, 1970-1980 - Osuna Castelán, Germán (El Colegio de México A.C., 1990)
The aim of this work is measuring the prevailing disparity in the economic and social development of the nation's federal entities and analyse their evolution during the 1970-1980 period. Multivaried stratification methodology was used for this end, in order to create groups of states with homogeneous living standards and calculate Atkinson indexes to measure the disparity in timing.The outcomes gathered indicte a decrease of the existing disparities in the spacial distribution of development during the 70s and show considerable potential benefits derived from a product redistribution policy at the territorial level.